Links between posttraumatic reactions, health effects, traumatic experiences and sense of coherence among Lithuanian survivors of political repression - Kazlauskas, Evaldas; Gailienė, Danutė (Psichologija, 2005)
Background: During Nazi and Soviet occupations in the years 1940–1958 one third of Lithuanian population were killed or deported to Siberia. Almost 300,000 people were deported to highly remote regions of Siberia. Former political prisoners and deportees experienced prolonged torture and persecutions, even after release from prison. Little is known in traumatic stress literature about effects of such extreme and prolonged traumatisation. The aim of the present study was to find out predictors of posttraumatic reactions in the group of survivors of political imprisonment. Methods: Former political prisoners (n = 724) were randomly selected from the national registry of Genocide and Resistance Research Centre of Lithuania. All former political prisoners are officially acknowledged as victims of Soviet repression by Lithuanian laws and are fully rehabilitated. The mean age of political prisoners was 75.8 (SD = 5,8) years. Questionnaires covering questions about lifetime traumatic experiences, exposure to political violence, posttraumatic symptoms as well as possible mediating factors between trauma and consequences have been mailed to participants of the study. Posttraumatic reactions were assessed using Lithuanian version of Traumatic Symptom Checklist (TSC-35). Results: Posttraumatic reactions correlated with demographic factors (gender, level of education), health effects, traumatic experiences and sense of coherence. Variables using hierarchical stepwise model were entered into multiple regression analysis. Demographic factors explained 8.1 % of posttraumatic reactions variance. Both health effects and demographic variables explained 19.6 % of variance. Traumatic experiences increased prediction of posttraumatic reactions to 31.6 %. Final equation, with sense of coherence entered on the fourth step, explained 43.7 % of posttraumatic symptom variance. Significant predictors of posttraumatic reactions among former Lithuanian political prisoners were: accumulative lifetime traumatic experiences, sense of coherence, gender (women showing higher levels of victimization), death of spouse, somatic complains immediately after imprisonment or forced deportation, and attribution of current poor health status to experienced political violence.
Keywords: trauma; political repression; posttraumatic stress; risk factors; long-term effects